Evidence Through a Glass, Darkly. Issue 1 (2nd January 2021) - Fritts, Megan
ABSTRACT: Dormandy's 'True Faith' presents two views on the proper epistemological stance towards faith: doxastic-partialism and evidentialism. Here, I argue for a third option that cuts across the evidentialism/partialism distinction. I first analyze the Pascalian conception of faith, arguing that Pascal begins with the cognitive attitude of acceptance rather than belief. Next, I discuss Dormandy's case for evidentialism, and contend that some evidence—the kind gained through transformative experiences—presents a difficulty for her argument. Finally, I offer my proposed view—Partialist Evidentialism—and argue that this approach is necessary for acquiring some unique kinds of evidence for religious faith.